Augmentation of antidepressants with bright light therapy ip patients with comorbid depression and borderline personality disorder - Praško, Ján; Brunovský, Martin; Látalová, Klára; Grambal, Aleš; Raszka, Michal; Vyskočilová, Jana; Závěšická, Lucie (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2010)
Backround. Borderline personality disorder (BPD) is typically characterized by instability and impairmed behaviour,-affectivity, interpersonal relations and lifestyle. The most common condition comorbid with BPD is a depressive-episode. Depression is associated with severe disturbance of the circadian rhythms. This is apparent in depressive-patients with BPD. Both sleep and diurnal rhythms are disturbed and the symptoms fluctuate. Bright light may be an-effective in treatment of seasonal affective disorder, circadian sleep disorder and jet lag. It also improves sleep-wake-patterns and behavioural disorders in hospitalized patients with Alzheimer’s disease. Several studies have suggested-antidepressant effects of phototherapy in non-seasonal depressive episodes. The treatment of comorbid depressive-disorder and borderline personality disorder (BPD) is usually reported to be less successful than the treatment of-patients without personality disorder. Studies describing the use of bright light in depressed patients with comorbid-BPD have not been published so far. Method. The aim of this open study was to assess the effectiveness of a 6-week combined therapy with the application-of bright light (10,000 lux, 6:30 to 7:30 a.m. for 6 weeks) added to SSRIs in drug-resistant depressed patients-with comorbid BPD who did not respond with improvement to 6-week administration of antidepressants. The study-comprised 13 female patients who met the ICD-10 diagnostic criteria for research and the DSM-IV-TR diagnostic-criteria for major depression. The participants were regularly evaluated using the CGI, HAMD and MADRS scales-and the BDI and BDI self-report inventories. Results. According to all the assessment instruments, the application of bright white light leads to a significant-improvement. However, the results must be interpreted with caution due to the open nature of the study.
Keywords: Female; Borderline Personality Disorder; Phototherapy; fototerapie; Financing, Organized; Humans; dospělí; Selective Serotonin Reuptake Inhibitors; lidé; depresivní porucha unipolární; Antidepressive Agents; Comorbidity; Treatment Outcome; ženské pohlaví; financování organizované; komorbidita; Depressive Disorder, Major; Adult; hraniční porucha osobnosti; selektivní inhibitory zpětného vychytávání serotoninu; výsledek terapie; antidepresiva